PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, AUDITOR SWITCHING DAN AUDIT TENURE PADA KUALITAS AUDIT - Muliawan, Eko Kurnia; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
A public accountant has an obligation to maintain and improve its audit quality in order to create public confidence in the accuracy and validity of the audited financial statements published by the auditor. Audit quality is used to improve the credibility of financial statements of users of accounting information so as to reduce the risk of non-credible information in the financial statements for users of financial statements. From the auditor's point of view, the audit is considered qualified if the auditor notices the general audit standards contained in the auditing standard statement including the professional qualities of the independent auditor, judgment used in auditing and the preparation of the audited financial statements. Some of the things that affect audit quality are the size of KAP, Auditor switching and audit tenure. The purpose of this research is to know and prove empirically the influence of KAP size to audit quality, Auditor switchingto audit quality, and audit of audit quality audit. This research was conducted at a banking company listed on BEI with observation year 2011-2015. The number of samples in this study were 30 banking companies. The data in this study is secondary data in the form of corporate financial statements obtained by non-participant observation method. This research used logistic regression analysys technique. The result found KAP size has positive effect on audit quality, while the switching auditor does not affect the quality of audit and audit tenure does not affect the quality of the audit. Keywords:    audit quality, KAP size, switching auditor, audit tenure